The Sky in Early Modern English Literature A Study of Allusions to Celestial Events in Elizabethan and Jacobean Writing, 1572-1620 - Levy, David H. (Springer New York : Imprint: Springer, 2011)
When a dissertation gets completed, the normal rule is that it is never read. By anyone.  David H. Levy's dissertation - The Sky in Early Modern English Literature:  A Study of Allusions to Celestial Events in Elizabethan and Jacobean Writing, 1572-1620 - is different.  It opens a whole new interdisciplinary field, which involves the beautiful relationship between the night sky and the works of the early modern period of English Literature.  Although the sky enters into much of literature through the ages, the period involving William Shakespeare and his colleagues is particularly rich.               When Shakespeare was about 8 years old, his father probably took him outside his Stratford home into their northward-facing back yard.  There, father and son gazed upon the first great new star visible in the past 500 years, shining forth as brightly as Venus, and even visible in daylight.  This new star, which we now know as a supernova, completely unhinged old ideas about the cosmos.  Combined with a parade of bright comets, a second bright new star in 1604, and a series of eclipses, people began to look at the sky more seriously.  In this book, Levy explores how the sky of that period was reflected in its literature.              Levy's ultimate goal in this book is to inspire his readers to do the same thing as their ancestors did so long ago-look at the sky and appreciate how those long-gone authors read the sky.